2023
DOI: 10.3389/fpubh.2022.1022055
|View full text |Cite
|
Sign up to set email alerts
|

Review of an intelligent indoor environment monitoring and management system for COVID-19 risk mitigation

Abstract: The coronavirus disease (COVID-19) outbreak has turned the world upside down bringing about a massive impact on society due to enforced measures such as the curtailment of personal travel and limitations on economic activities. The global pandemic resulted in numerous people spending their time at home, working, and learning from home hence exposing them to air contaminants of outdoor and indoor origins. COVID-19 is caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which spreads by ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Instead, in terms of group size, there seemed to be a threshold above 10 participants that needed to be crossed to see an increase in CO2 concentration levels. Regarding the level of physical activity in the room, the result seemed contradictory: The higher intensity of physical activity exerted by the participants in G2 did not significantly affect the CO2 levels due to exhalation and resulted in a lower average CO2 concentration (Wiryasaputra et al, 2023;Rowe et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Instead, in terms of group size, there seemed to be a threshold above 10 participants that needed to be crossed to see an increase in CO2 concentration levels. Regarding the level of physical activity in the room, the result seemed contradictory: The higher intensity of physical activity exerted by the participants in G2 did not significantly affect the CO2 levels due to exhalation and resulted in a lower average CO2 concentration (Wiryasaputra et al, 2023;Rowe et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Smart-working and remote lectures were maintained for vulnerable workers with an individual susceptibility to infections. Since air quality of indoor public places impacts the spread of COVID-19, all premises of the University of Trieste were subject to enhanced ventilation and low-cost sensors for intelligent monitoring of indoor CO 2 , were considered to mitigate the spread of SARS-CoV-2 and prevent common symptoms such as coughs, headaches, eye irritation, dizziness and fatigue [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on more than 100,000 workers during the first pandemic wave in Germany reported an increased risk of COVID-19 in essential occupations such as healthcare, logistics, transport, police, jurisdiction and public administration and in higher-occupational-status positions (e.g., managers and highly skilled workers) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fieldwork using CO 2 sensors as a countermeasure against airborne transmission has been conducted worldwide. Wiryasaputra et al [ 21 ] conducted a systematic review of studies that monitored indoor environments, particularly CO 2 , to reduce the risk of COVID-19 infection. According to a systematic review of 19 articles in urban spaces, CO 2 is the primary reference for the spread of novel coronaviruses in buildings [ 22 ].…”
Section: Introductionmentioning
confidence: 99%